Cardiovascular Disease in Relation to Placental Abruption: A Population‐Based Cohort Study from Denmark. Issue 3 (21st February 2017) - Ananth, Cande V.; Hansen, Anne Vinkel; Williams, Michelle A.; Nybo Andersen, Anne‐Marie
Abstract: Background: Cardiovascular (CVD) complications stemming from vascular dysfunction have been widely explored in the setting of preeclampsia. However, the impact of abruption, a strong indicator of microvascular disturbance, on the risk of CVD mortality and morbidity remains poorly characterised. Methods: We designed a cohort analysis of 828 289 women who delivered singletons in Denmark between 1978 and 2010. We linked the National Patient Registry and the Registry of Causes of Death to the Danish Birth Registry to ascertain CVD events. We estimated CVD risks in relation to abruption from Cox proportional hazards regression following adjustments for confounders. Results: With 13 231 562 person‐years of follow‐up of women with at least one delivery, 11 829 pregnancies were complicated by abruption. The median (interquartile range) follow‐up in the non‐abruption and abruption groups was 16 (8, 24) and 18 (10, 25) years, respectively. CVD mortality rates in women with and without abruption were 0.9 and 0.3 per 10 000 person‐years, respectively (adjusted hazard ratio (HR) 2.7, 95% confidence interval (CI) 1.5, 5.0). The corresponding CVD morbidity complication rates were 16.7 and 10.0 per 10 000 person‐years, respectively (HR 1.5, 95% CI 1.4, 1.8). The increased risks were evident for ischaemic heart disease, acute myocardial infarction, hypertensive heart disease, non‐rheumatic valvular disease, and congestive heart failure. Conclusions: This study shows increased hazards of CVD morbidity and mortality in relation to abruption. A better understanding of the pathogenesis of distorted placental microvasculature is needed as this appears to be a harbinger of CVD later in life.